Radii of Epichloë festucae colonies treated with saliva or water measured every 8 hours - Tanentzap, Andrew J.; Vicari, Mark; Bazely, Dawn R. (Dryad Digital Repository, 2014)
We tested whether application of reindeer and moose saliva reduced in vitro growth of Epichloë festucae colonies relative to a control treatment of distilled water. We isolated E. festucae from Festuca rubra, grown from natural populations in northern Sweden, by cutting the base of the youngest fully-extended leaf in each plant. Sections were surface sterilized and embedded in potato dextrose medium with 60 mg/L of penicillin G and streptomycin. Plates were stored in the dark at 24°C for 2 weeks. We then assigned 22-25 colonies per treatment, with 5-9 replicates of three plant genotypes, and recorded the initial radius of each plate. Saliva was applied and we measured colony radius relative to the baseline every 8 hours over 2 days.